EXPERIMENTAL STUDY AND PERFORMANCE OF PERMANENT MAGNET AND WOUNDED TYPE DC MOTOR USING OF REGULATOR - Mahobia, Tanu; Kori, Dr. A. K. (International Journal of Engineering Technologies and Management Research, 2016)
The DC motor has important role in moving system because of mostly use in the industry. The speed control of DC motor is increasingly getting sophisticated and precise. The Speed of the DC motor is controlled by with the help of controlling the armature voltage. There are various methods of speed control of DC drives namely field control, armature voltage control.